Fintrac's mobile office: delivering agribusiness support in Honduras - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
by Charles Mahoney Charles Mahoney describes how Honduran extension officers have been equipped with a wide range of ICTs to support smallholder farmers after the devastation caused by Hurricane Mitch. ICTs such as a global positioning syste